Correction of left displaced abomasal by videolaparoscopy. - Leiva, C JM (Universidad Nacional del Litoral, 2021)
Correction of left abomasal displacement by video laparoscopy. This article reviews the benefits of the laparoscopic abomasopexy used for correction and fixation of the left abomasal displacement in dairy cows. The first steps are similar to the conventional technique, with sedation, analgesia and antisepsis. Two small flank incisions were made, the first one is about 10 centimeters ventral to the lumbar transverse processes in the cranial aspect of the left paralumbar fossa, and the second one, more cranial than the other and is located 7 cm ventral to the transverse processes of the lumbar vertebrae in the left 11th intercostal space, these two are the entry points of instruments and optics. This technique allows us to shorten the surgical time, reducing the tissue exposure time, the possibility of intra and post-surgical infections and iatrogenic injuries. Therefore, we saw that the recovery time was shorter; and a quick return to production is guaranteed due to the low use of antibiotics.